Interactions of an Emerging Fungal Pathogen Scedosporium aurantiacum with Human Lung Epithelial Cells - Jashanpreet Kaur (Nature Portfolio, 2019)
Abstract Scedosporium fungi are found in various natural and host-associated environments, including the lungs of cystic fibrosis patients. However, their role in infection development remains underexplored. Here the attachment of conidia of a virulent S. aurantiacum strain WM 06.482 onto the human lung epithelial A549 cells in vitro was visualized using microscopy to examine the initial steps of infection. We showed that 75–80% of fungal conidia were bound to the A549 cells within four hours of co-incubation, and started to produce germ tubes. The germinating conidia seemed to invade the cells through the intercellular space, no intracellular uptake of fungal conidia by the airway epithelial cells after conidial attachment. Transcriptomic analysis of the A549 cells revealed that the up-regulated genes were mainly associated with cell repair and inflammatory processes indicating a protective response against S. aurantiacum infection. Network analysis of the differentially expressed genes showed activation of the innate immune system (NF-kB pathway) leading to the release of pro-inflammatory cytokines. We believe this is the first report showing the transcriptomic response of human alveolar epithelial cells exposed to S. aurantiacum conidia paving a way for better understanding of the mechanism of the infection process.